2022
DOI: 10.1016/j.jtcvs.2021.03.120
|View full text |Cite
|
Sign up to set email alerts
|

External stenting and disease progression in saphenous vein grafts two years after coronary artery bypass grafting: A multicenter randomized trial

Abstract: Objectives: Little data exist regarding the potential of external stents to mitigate long-term disease progression in saphenous vein grafts. We investigated the effect of external stents on the progression of saphenous vein graft disease.Methods: A total of 184 patients undergoing isolated coronary artery bypass grafting, using an internal thoracic artery graft and at least 2 additional saphenous vein grafts, were enrolled in 14 European centers. One saphenous vein graft was randomized to an external stent, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…The rationale for this intervention is manifold and includes mitigation of the wall stretch induced by abrupt conduit arterialization when transposing it from a low-pressure venous system to a high-pressure arterial circuit, enhancement of lumen uniformity and conduit-to-target size matching, and induction of adventitial neovascularization . Early trials of this technology have yielded promising results …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for this intervention is manifold and includes mitigation of the wall stretch induced by abrupt conduit arterialization when transposing it from a low-pressure venous system to a high-pressure arterial circuit, enhancement of lumen uniformity and conduit-to-target size matching, and induction of adventitial neovascularization . Early trials of this technology have yielded promising results …”
Section: Discussionmentioning
confidence: 99%
“…Although this external support device would not be expected to reduce the risk of short-term SVG occlusion caused by intraoperative technical factors, it may increase SVG intermediate to long-term patency by limiting graft IH. Recent small trials of this device using intravascular ultrasound (IVUS) have demonstrated a reduction in IH and graft irregularity, markers of early graft disease . Based on this preliminary evidence, we conducted a randomized clinical trial to assess the effect of the device in reducing IH and SVG irregularity in patients undergoing CABG for multivessel coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…The development of external stents emerges as an approach to limit the hyperdistention of venous grafts, therefore minimizing the pathologic changes resulting from “venous remodeling.” 1 , 2 Taggart and colleagues, 1 in their relevant multicenter and randomized study, presented similar patency between SV grafts with or without application of external stents, illustrating a reduced degree of parietal irregularities and intimal hyperplasia in venous grafts in which an external stent was used, in 2 years of follow-up.…”
mentioning
confidence: 91%
“…In summary, we congratulate Taggart and colleagues 1 for the valuable article, and for the effort to improve the results obtained with the venous grafts. We emphasize, however, that the adoption of other technical approaches, such as composite grafts, might be more economically feasible and considerably more physiological to improve CABG results.…”
mentioning
confidence: 91%
“…In a recent randomized trial reporting on the effect of external stenting on saphenous vein grafts (SVG) disease, Taggart and colleagues 1 demonstrated that this technique improved Fitzgibbon patency scales and significantly reduced intimal hyperplasia area and thickness after a 2-year follow-up, although no difference in overall patency rates was observed between the stented and nonstented SVG (78.3% vs 82.2%, P = .43). 1 …”
mentioning
confidence: 99%